A Novel Approach to PID Controller Design for Improvement of Transient Stability and Voltage Regulation of Nonlinear Power System - Rekha Chaudhary; Arun Kumar Singh; Saligram Agrawal (Institute of Advanced Engineering and Science, 2016)
In this paper, a novel design method for determining the optimal PID controller parameters for non-linear power system using the particle swarm optimization (PSO) algorithm is presented. The direct feedback linearization (DFL) technique is used to linearize the nonlinear system for computing the PID (DFL-PID) controller parameters. By taking an example of single machine infinite bus (SMIB) power system it has been shown that PSO based PID controller stabilizes the system and restores the pre-fault system performance after fault is cleared and line is restored. The performance of this controlled system is compared with the performance of DFL-state feedback controlled power system. It has been shown that the performance of DFL-PID controlled system is superior compared to DFL-state feedback controlled system. For simulation MATLAB 7 software is used.